Barry Commoner papers - Commoner, Barry, 1917-2012.
Correspondence, diaries, speeches, writings, research files, subject files, organizational files, slides, photographs, and other papers documenting Commoner's career as a biologist, ecologist, and environmental activist. Subjects include the physiochemical basis of biological processes and the moral obligations of scientists.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Biologist, ecologist, and environmental activist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Biology; Ecology; Environmentalism; Science -- Moral and ethical aspects; Biologists; Ecologists; Environmental activists